Transforming Latin America : the international and domestic origins of change - Arceneaux, Craig L., 1965- (Pitt Latin American series., 2005)
"This ambitious book offers a clear and unified framework for understanding political change across Latin America. The impact of U.S. hegemony and the global economic system on the region is widely known, and scholars and advocates alike point to Latin America's vulnerability in the face of external forces. In spite of such foreign pressure, however, individual countries continue to chart their own courses, displaying considerable variation in political and economic life."